The effect of social media marketing on brand loyalty in the hospitality industry in Zimbabwe: the moderating role of age - Wilbert Manyanga; James Kanyepe; Lovemore Chikazhe; Tendai Manyanga (Cogent Business & Management, 2024)
Building and maintaining brand loyalty is crucial for every organisation in such competitive business environment and organisations in the hospitality industry are not spared. Hotels have made many efforts on branding to gain brand loyalty from their customers and recently they have carried their efforts to social media to survive in online environment as well. The growth in social media marketing is attributed to the increase in social networking users, internet users, mobile phone users and digital content consumption. Therefore, the aim of this study was to establish the effect of social media marketing on brand loyalty in the hospitality industry in Zimbabwe, with age as a moderator. Data was gathered from 223 hotel customers using a structured questionnaire with Likert-type questions. The findings show that social media marketing positively influences brand loyalty in emerging market. Also, the study findings show that age moderate the effect of social media marketing on brand loyalty. The study contributes to studies that proved a significant relationship between social media marketing and brand loyalty by including the moderating role of age. Thus, hospitality organisations are advised to utilise social media marketing in order to improve brand loyalty. In addition, they must consider the moderating role of age when formulating social media marketing strategies to enhance brand loyalty.Social media marketing contributes a crucial role in the success of firms in the hospitality industry. This study examines effect of social media marketing on brand loyalty within the hospitality industry in Zimbabwe and the moderating role of age. The study specifically tests the effect of social media, media sharing networks and consumer review networks on brand loyalty. The study established that social media marketing positively influences brand loyalty in emerging market. Also, the study established that age moderates the relationship between social media marketing and brand loyalty. Thus, hospitality organisations are encouraged to utilise social media marketing in order to improve brand loyalty. Also, they are advised to consider age when formulating strategies to enhance brand loyalty.
Keywords: 650; Brand loyalty; consumer review networks; hospitality; media sharing networks; social media marketing; Zimbabwe